Preparation and Characterization of Chitosan Membranes from Crab Shells (Scylla olivacea) for Beverage Preservative - Reni Mulyani; Dikdik Mulyadi; Nopriana Yusuf (Syarif Hidayatullah State Islamic University, 2019)
Chitosan can extend the shelf life of food and can be used in food preservation. Chitosan is derived from the shell of the animal crustacean, and is a derivative of the chitin polymer. This study aimed to determine the effectiveness of the use of chitosan membrane as an antibacterial compound and its application in pineapple juice products. Chitosan isolation is carried out through three stages, namely deproteination, demineralization, and deacetylation. Determination of the degree of deacetylation using the infrared spectroscopy method and the preservative effectiveness test was carried out based on SNI 01-2332.3-2006 concerning the testing of the Total Plate Count (ALT). Crab chitosan obtained from white-brown isolation results, soluble in 1% acetic acid and the value of the degree of deacetylation (DD) of chitosan crab is 81%. The addition of 1.5% crab chitosan membrane to pineapple juice can reduce bacterial growth until the 20th day with a total plate value (ALT) of 9.1x103 CFU / ml.